2016
DOI: 10.1002/cphc.201600051
|View full text |Cite
|
Sign up to set email alerts
|

1,1‐Dilithioethylene: Toward Spectroscopic Identification of the Definitive Singlet Ground Electronic State of a Peculiar Structure

Abstract: 1,1-Dilithioethylene is a prototypical carbon-lithium compound that is not known experimentally. All low-lying singlet and triplet structures of interest were investigated by using high-level theoretical methods with correlation-consistent basis sets up to pentuple ζ. The coupled cluster methods adopted included up to full triple excitations and perturbative quadruples. In contrast to earlier studies that predicted the twisted C2v triplet to be the ground state, we found a peculiar planar Cs singlet ground sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The natural atomic charges are shown in parentheses, and the Wiberg bond indices are shown in square brackets. Structure 1 was reported earlier in ref .…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The natural atomic charges are shown in parentheses, and the Wiberg bond indices are shown in square brackets. Structure 1 was reported earlier in ref .…”
Section: Resultsmentioning
confidence: 74%
“…The earlier theoretical studies of dilithioethene have been reported by Schleyer, Pople, et al in 1976, then by Schleyer, Schaefer, et al in the 1990s, , and then by Röthlisberger and Klein in 1995 . Recently, we have studied the possible stationary points of 1,1-dilithioethylene (H 2 CCLi 2 ) at the CCSD­(T)/cc-pVQZ level of theory and predicted the energetics at the CCSDT­(Q)/CBS level . The singlet ethylene-like H 2 CCLi 2 structure ( C 2 v ) is actually a transition state, rather than a minimum, with one imaginary vibrational frequency that corresponds to the CCLi bending mode.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Of course, twisted double bonds also may be achieved through electronic effects, ie, by involving electropositive atoms such as lithium or silicon. For example, 1,1‐dilithioethylene was first suggested by Apeloig, Schleyer, and Pople to have a triplet D 2 d structure, and recent studies based on high‐level ab initio calculations document a modest singlet‐triplet gap (9.0 kcal/mol) . Our exploration excludes these examples but focuses on hydrocarbons with twisted double bonds.…”
Section: Introductionmentioning
confidence: 99%